Teknologi Akuaponik sebagai Home Farm untuk Meningkatkan Ketahanan Pangan di Desa Tampingmojo - Umi Kulsum Nur Qomariah; Mazidatul Faizah; SIti Aminatuz Zuhria; Moh Andrik Robil Alamsyah; Sindi Yulia Anggraini; M Arsyad Amrullah (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2022)
Agriculture is an important foundation in the fulfillment of food commodities. Meeting household food needs is an important foundation for achieving food security. However, not all people in Tampingmojo Village, Tembelang District, Jombang Regency have agricultural land to be able to meet their food needs, especially agricultural land in Tampingmojo Village has decreased since the construction of the Mojokerto - Kertosono toll road, so that the supply of food commodities such as vegetables and fish depends on supplies from outside the village. Tampingmojo. Aquaponics is a solution for food security for the Tampingmojo village community. This community service purpose to introduce Aquaponics Technology to the Tampingmojo village community by utilizing available local resources. The targeted community for this activity is a group of PKK women and Karang Taruna youth in the village of Tampingmojo. The method used is Participatory Action Research (PAR) which is carried out in 3 stages, there are preparation, implementation and evaluation. The results of the evaluation showed that 80% of the post-test questions could be answered by participants and the delivery of simple aquaponic technology materials was well received and could be applied with the available resources in Tampingmojo village.